2014
DOI: 10.1177/1321103x14560320
|View full text |Cite
|
Sign up to set email alerts
|

Connecting through music: The contribution of a music programme to fostering positive youth development

Abstract: This article reports an investigation of the musical and extra-musical outcomes of participation in a music programme for students in four socio-economically disadvantaged school settings. Drawing on the theory of Positive Youth Development, which provides a focus on the positive assets young people bring to their engagement rather than perceived deficits and risks, the findings indicate that PYD outcomes do arise from music participation in these settings. Specifically, students evidence developing competenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 40 publications
4
46
0
2
Order By: Relevance
“…Research has consistently found that creating music has positive psychological effects for all ages from children to older adults. Music makers have improved selfesteem, perception of self-worth and perceived quality of life; this may be because of an increased sense of purpose, accomplishment and identity associated with music making (Barrett, 2014;Croom, 2014;Hallam et al, 2014). Performing and creating music in groups can provide additional benefits for individuals, giving participants an increased sense of pride and accomplishment, increased social satisfaction and affirmation, which includes positive social relationships (Bailey, 2005;Susan Hallam et al, 2014).…”
Section: Benefits Of Music Makingmentioning
confidence: 99%
“…Research has consistently found that creating music has positive psychological effects for all ages from children to older adults. Music makers have improved selfesteem, perception of self-worth and perceived quality of life; this may be because of an increased sense of purpose, accomplishment and identity associated with music making (Barrett, 2014;Croom, 2014;Hallam et al, 2014). Performing and creating music in groups can provide additional benefits for individuals, giving participants an increased sense of pride and accomplishment, increased social satisfaction and affirmation, which includes positive social relationships (Bailey, 2005;Susan Hallam et al, 2014).…”
Section: Benefits Of Music Makingmentioning
confidence: 99%
“…Sport is the most commonly chosen ECA activity (Feldman & Matjasko, 2007) with the most research available, detailing its positive impact on aspects of PYD. Nonetheless, participation in music has been reported to bring benefits in terms of personal identity exploration; understanding emotions; opportunities to respond to challenges and appropriate risk-taking through public performance; development of life-skills and character; and increased social skills through connections with peers and adult leaders (Barrett & Bond, 2015;Barrett & Smigiel, 2007;Campbell, Connell, & Beegle, 2007;Ter Bogt, Mulder, Raaijmakers, & Gabhainn, 2010).…”
Section: List Ofmentioning
confidence: 99%
“…Hence, extra-curricular sport and music participation were chosen as the settings for this research. These activities are considered to present challenges and demands that may contribute to building character and although research evidence is more plentiful for sport than music ECAs (Fredricks et al, 2002), they have been previously suggested to offer settings which support aspects of positive development for youth (Barber, Eccles, & Stone, 2001; Barrett & Bond, 2015;Eccles, Barber, Stone, & Hunt, 2003), The picture is not entirely consistent, however, as studies have found associations between sport participation and negative behaviours (Barber et al, 2001), and creative arts participation has been found to be negatively related with PYD outcomes (Bundick, 2011). Thus, a need for research into the relation between sport and music ECAs and the PYD C of character is indicated.…”
Section: List Ofmentioning
confidence: 99%
See 2 more Smart Citations